Tongue reduction in Beckwith–Wiedemann syndrome: outcome and treatment algorithm - Naujokat, H.; Möller, B.; Terheyden, H.; Birkenfeld, F.; Caliebe, D.; Krause, M.F.; Fischer-Brandies, H.; Wiltfang, J. (International journal of oral and maxillofacial surgery, 2019)
Beckwith–Wiedemann syndrome is a rare congenital overgrowth disorder with macroglossia being one of the cardinal symptoms. In pronounced cases, macroglossia can lead to airway obstruction, musculoskeletal alterations and functional deficits. Surgical tongue reduction is performed at varying ages and with different techniques. This study evaluated perioperative complications, as well as long-term aesthetic and functional outcomes, in a large cohort. A total of 68 patients, treated either surgically or conservatively, were included. Depending on the severity of macroglossia, patients were divided into three groups to determine the treatment algorithm. Complications after surgical tongue reduction were prolonged intubation and revision due to dehiscence or haematoma. In the long term, no patient suffered from impaired sense of taste or paresthesia, although the shape of the tongue was disproportional in 85%. With the present treatment algorithm, operative tongue reduction exerts a positive influence on skeletal, dentoalveolar and functional development with sufficient long-term outcome and high grade of satisfaction of the patients. Supportive therapy in an interdisciplinary centre is of fundamental importance for both surgical and conservative treatment.